The Uncinate Process First Approach in Laparoscopic Pancreaticoduodenectomy: A Single-institution Experience - Zhang, Yue; Sun, Dong-Lin; Chen, Xue-Min (Surgical laparoscopy, endoscopy & percutaneous techniques, 2017)
Limited studies regarding the uncinate process first in laparoscopic pancreaticoduodenectomy (LPD) have been reported. The objective of this study was to evaluate the feasibility, safety, and efficacy of LPD using the uncinate process first approach. This is a retrospective study of selected patients who underwent LPD using the uncinate process first approach at our center between between June 2015 and January 2017. Clinical characteristics and intraoperative and postoperative data were retrospectively analyzed. LPD was performed successfully in 45 patients. The median operative time was 410±68 minutes and the median loss of blood was 258±50 mL. Intraoperative frozen section histologic analyses revealed that margin-negative resections were negative in all cases. The median first flatus time was 2±1 day, and median diet start time was 3±1.5 day. The median postoperative hospital stay was 13±4 day. There were no deaths within 30 days following LPD. The mean number of lymph nodes removed was 20±5. The overall morbidity rate was 20%. LPD with the uncinate process first approach well combines the benefits of laparoscopy with low risk of postoperative complications and high rate of curative resection.